Application of the Enzyme-linked Immunosorbent Assay Procedure to the Detection of Grapevine Fanleaf Virus - Engelbrecht, D. J. (South African Journal of Enology and Viticulture, 2017)
Enzyme-linked immunosorbent assay was used to detect grapevine fanleaf virus (GFV) directly in grapevine leaf tissue. The addition of nicotine or nicotine and sodium diethyldithiocarbamate to the extracting buffer solution greatly enhanced the sensitivity of the procedure and enabled detection of GFV concentrations as low as 12 ng/m t The conjugated GFV gamma-globulin detected the GFV strains, grapevine vein banding and grapevine yellow mosaic but failed to detect the GFV serotype arabis mosaic in grapevine leaf tissue. The technique makes possible the collection and processing of numerous samples throughout the growing season and is, therefore, particularly suitable for studies on the incidence and spread of GFV in the field. It also facilitates the resolution of disease syndromes with which GFV is associated.